2002
DOI: 10.1271/bbb.66.828
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Transport of Dietary Cholesterol Oxidation Products, Cholesterol and Triacylglycerols in Rats

Abstract: Rats were fed on a diet containing 0.5% cholesterol oxidation products (oxysterols) or 0.5% cholesterol for 30 min, and their lymph was collected for 7 h. The amount of each of the individual oxysterols absorbed in the lymph depended on the ingested amounts, but the recovery was the highest for 5alpha,6alpha-epoxycholesterol (10.5%), this being followed by 7-ketocholesterol (5.8%), cholestanetriol (5.2%), 7beta-hydroxycholesterol (4.8%), 7alpha-hydroxycholesterol (3.4%), 5beta,6beta-epoxycholesterol (2.2%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Peak identification was confirmed by relative retention time and mass spectral comparison with authentic standards, as well as with the NIST/EPA/NIH mass spectral database library (NIST'02 ASC1 version, Gaithersburg, MD, USA). As reported elsewhere (Tomoyori et al 2002), oxysterols were grouped into seven 'time windows': group 1 17 -20 min (5a-cholestane); group 2 20-27 min (7a-hydroxycholesterol); group 3 27-29•7 min (7b-hydroxycholesterol, b-epoxycholesterol, a-epoxycholesterol); group 4 29•7-32 min (unidentified compounds); group 5 32-34•2 min (cholestanetriol); group 6 34•2-36•5 min (7-ketocholesterol, 25-hydroxycholesterol); group 7 36•5-42•5 min (27-hydroxycholesterol). Several variables including ions monitored, relative retention time, correlation coefficient for calibration curves, response factors for the monitored ions, detection limit and CV for repeated injections have been reported elsewhere (Tomoyori et al 2002).…”
Section: Determination Of Oxysterolssupporting
confidence: 57%
“…Peak identification was confirmed by relative retention time and mass spectral comparison with authentic standards, as well as with the NIST/EPA/NIH mass spectral database library (NIST'02 ASC1 version, Gaithersburg, MD, USA). As reported elsewhere (Tomoyori et al 2002), oxysterols were grouped into seven 'time windows': group 1 17 -20 min (5a-cholestane); group 2 20-27 min (7a-hydroxycholesterol); group 3 27-29•7 min (7b-hydroxycholesterol, b-epoxycholesterol, a-epoxycholesterol); group 4 29•7-32 min (unidentified compounds); group 5 32-34•2 min (cholestanetriol); group 6 34•2-36•5 min (7-ketocholesterol, 25-hydroxycholesterol); group 7 36•5-42•5 min (27-hydroxycholesterol). Several variables including ions monitored, relative retention time, correlation coefficient for calibration curves, response factors for the monitored ions, detection limit and CV for repeated injections have been reported elsewhere (Tomoyori et al 2002).…”
Section: Determination Of Oxysterolssupporting
confidence: 57%
“…However, studies of the delivery of exogenous oxysterols to humans and animals have demonstrated little to no accumulation in host tissues. Depending on the specific oxysterol, this may reflect either a poor rate of absorption or an efficient hepatic conversion to more polar metabolites which are excreted (reviewed elsewhere 1,2 and supported by more recent studies [6][7][8][9][10][11] ).…”
Section: Oxysterols From Foodmentioning
confidence: 94%
“…7,8) The diet was based on the AIN-93G diet formulation, 14) as previously described. 9) The mice were individually housed in a temperature-controlled room at 21-23 C with a light-dark cycle (light on 8:00-20:00).…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] These sterol oxidation products are transported to the circulation via the lymphatic system after being absorbed by the small intestine. 6,8,9) It is expected that each oxysterol has a different biological effect in the body, but this remains to be elucidated.…”
mentioning
confidence: 99%